2016
DOI: 10.1007/s11145-016-9659-3
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic skills important to Chinese literacy development: the role of radical representation and orthographic memory of radicals

Abstract: A 3-year longitudinal study among 239 Chinese students in Grades 2-4 was conducted to investigate the relationships between orthographic skills (including positional and functional knowledge of semantic radicals and phonetic radicals, and orthographic memory of radicals) and Chinese literacy skills (word reading, word spelling, reading comprehension and written composition). Phonetic radical knowledge was the only significant longitudinal predictor of word reading, whereas all orthographic skills examined were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 42 publications
(67 reference statements)
1
12
0
Order By: Relevance
“…Thus, semantic radicals are functionally more reliable than phonetic radicals (Shen, 2010). Yeung and colleagues (2016) found that knowledge of the positional and functional properties of semantic radicals is a stronger predictor of Chinese reading comprehension than knowledge of phonetic radicals. Tong and colleagues (2017) also reported that Chinese children’s character recognition strategies tend to change over time, evolving from reliance on the positional and phonological cues of radicals towards greater reliance on the radicals’ semantic cues.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, semantic radicals are functionally more reliable than phonetic radicals (Shen, 2010). Yeung and colleagues (2016) found that knowledge of the positional and functional properties of semantic radicals is a stronger predictor of Chinese reading comprehension than knowledge of phonetic radicals. Tong and colleagues (2017) also reported that Chinese children’s character recognition strategies tend to change over time, evolving from reliance on the positional and phonological cues of radicals towards greater reliance on the radicals’ semantic cues.…”
Section: Introductionmentioning
confidence: 95%
“…Orthographic knowledge has been found to be a significant predictor of immediate and long-term Chinese character recognition, word reading, sentence comprehension and even text-level literacy (Mori, 2014; Williams & Bever, 2010; Yeung et al, 2013, 2016). Furthermore, different components of orthographic knowledge are found to have differential impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Acquisition of orthographic codes including letter identity and relative letter positions underlie literacy development in alphabetic languages, and many researchers have also suggested that literacy in Chinese poses high demands on visual and spatial analysis (e.g., Cole & Pickering, ; McBride‐Chang et al, ; Yeung, Ho, Chan, & Chung, ). Orthographic processing is integral to both reading acquisition in Chinese children (e.g., Shu, Chen, Anderson, Wu, & Xuan, ) and character recognition in skilled Chinese readers (e.g., Chen, Allport, & Marshall, ; Taft & Zhu, ).…”
mentioning
confidence: 99%
“…It is also helpful to encourage young children to actively engage with print during shared book reading with the print-referencing strategies as well (Gong and Levy, 2009; Justice et al, 2005; Piasta et al, 2012). Secondly, if adults’ goal is to enhance young children’s RA, their resources should also be devoted to enhancing young children’s OA, which is especially important for Chinese literacy development (Yeung et al, 2016). The fact that both fixation on print and OA are important to children’s RA in the present study gives evidence for the balanced approach in early literacy education.…”
Section: Discussionmentioning
confidence: 99%